Supplementary Effects of Allium hookeri Extract on Glucose Tolerance in Prediabetic Subjects and C57BL/KsJ-db/db Mice - Ji-Su Kim; Hyun-Ju Kim; Eun-Byeol Lee; Ji-Hye Choi; Jieun Jung; Hwan-Hee Jang; Shin-Young Park; Ki-Chan Ha; Yu-Kyung Park; Jong-Cheon Joo; Sung-Hyen Lee (Pharmaceuticals, 2023)
Allium hookeri (AH) has been used as a nutritional and medicinal food in Asia for many years. Our previous studies have described its anti-diabetic, anti-obesity, and anti-inflammatory activities in animal models and prediabetes. This study investigated whether AH could improve glycemia by modulating insulin secretion in prediabetic subjects through an in-depth study. Eighty prediabetic subjects (100 ≤ fasting plasma glucose < 140 mg/dL) were randomly assigned to a placebo (n = 40) group or an ethanol AH extract (500 mg/day, n = 40) group for 12 weeks. Dietary intake and physical activity, blood glucose (an oral glucose tolerance test for 120 min), insulin (insulin response to oral glucose for 120 min), area under the curve (AUC) of glucose or insulin after oral glucose intake, insulin sensitivity markers, C-peptide, adiponectin, glycated hemoglobin A1c (HbA1c) levels, hematological tests (WBC, RBC, hemoglobin, hematocrit, and platelet count), blood biochemical parameters (ALP, AST, total bilirubin, total protein, albumin, gamma-GT, BUN, creatinine, LD, CK, and hs-CRP), and urine parameters (specific gravity and pH) were examined at both baseline and 12 weeks after supplementation with placebo or AH capsules. Fifty-eight participants (placebo group: 20 men and 10 women; AH group: 13 men and 15 women) completed the study. AH supplementation moderately reduced postprandial blood glucose at 60 min (−6.14 mg/dL, p = 0.061), postprandial insulin levels at 90 min (−16.69 µU/mL, p = 0.017), the glucose AUC at 90 min (−412.52 mg*min/dL, p = 0.021), as well as the insulin AUC at 90 min (−978.77 µU*min/mL, p = 0.021) and 120 min (−1426.41 µU*min/mL, p = 0.015) when compared with the placebo group. However, there were no effects of AH on dietary intake and physical activity; HOMA index; HbAlc; C-peptide; or adiponectin, hematological-, blood biochemical-, and urinary markers. To confirm the effects of AH extract on blood glucose insulin sensitivity, C57BL/6J or C57BL/KsJ-db/db mice were used (n = 8/group). Body weight, fasting plasma glucose level, lipid profiles, liver and renal function, pancreatic histology, and insulin immunoreactivity were assessed. In the diabetic db/db mice, hyperglycemia, which was accompanied by an increase in insulin secretion in diabetic mice, was significantly reduced by AH treatment, resulting in the alleviation of β-cell overcompensation and insulin resistance. We confirmed that AH supplementation can effectively control blood glucose and insulin levels by improving insulin sensitivity and may be a potential agent for glycemic control in subjects with prediabetes and type 2 diabetes mellitus.